Hubungan Pemberian Pisang Ambon Terhadap Penurunan Intensitas Mual Dan Muntah Ibu Hamil Trimester 1 Di Klinik Pratama Vina Tahun 2024 - Setiawati, Irka; Yelni, Afrida; Khoiriyani, Kiki (Universitas Prima Indonesia, 2024)
Pregnancy is a condition where in a woman's womb there is an embryo or fetus. Physiological changes that pregnant women often experience, such as fatigue, stomach cramps, frequent urination, morning sickness and nausea, vomiting. According to the World Health Organization (WHO), the incidence of nausea and vomiting in the world is 70% -80% of the number of pregnant women. The incidence of emesis gravidarum is at least 15% of all pregnant women. The frequency of morning sickness is not only in the morning but can be in the afternoon or even at night. Based on a preliminary survey conducted at Pratama Vina Clinic in February 2024, 23 pregnant women were found to experience nausea and vomiting. Consuming Ambon Bananas can be a cheap and practical non-pharmacological alternative. The general aim of this research is to determine the relationship between giving Ambon bananas and reducing the intensity of nausea and vomiting in pregnant women in the 1st trimester at Pratama Vina Clinic in 2024. This research is a type of quantitative research with a Quasi-Experimental research design with a One Group Pretest-Posttest design. The population in this study consisted of 15 pregnant women in the first trimester who came for a pregnancy visit. The sampling technique in this research was Accidental Sampling of 15 people. This research used the T-Test to obtain a p-value <0.000. This shows that there is a relationship between giving Ambon bananas to reducing the intensity of nausea and vomiting in pregnant women in the 1st trimester at the Pratama Vina clinic in 2024, due to the effect of the B6 content, the benefits of B6 as a coenzyme for reactions in metabolism, in protein synthesis and metabolism, especially serotonin is useful for reducing nausea, vomiting.